Comparison of human‐induced pluripotent stem cells and mesenchymal stem cell differentiation potential to insulin producing cells in 2D and 3D culture systems in vitro. Issue 5 (15th October 2019) - Abazari, Mohammad Foad; Nasiri, Navid; Nejati, Fatemeh; Zare Karizi, Shohreh; Amini Faskhodi, Mojdeh; Saburi, Ehsan; Aghapur, Nasrin; Mahdavi, Mohammad Reza; Ardeshirylajimi, Abdolreza; Enderami, Seyed Ehsan; Soleimanifar, Fatemeh
Abstract: Diabetes is one of the most common diseases in the world that is chronic, progressive, and costly, and causes many complications. Common drug therapies are not able to cure it, and pancreas transplantation is not responsive to the high number of patients. The production of the insulin producing cells (IPCs) from the stem cells in the laboratory and their transplantation to the patient's body is one of the most promising new approaches. In this study, the differentiation potential of the induced pluripotent stem cells (iPSCs) and mesenchymal stem cells (MSCs) into IPCs was compared to each other while cultured on poly(lactic‐co‐glycolic) acid (PLGA)/polyethylene glycol (PEG) nanofibrous scaffold as a 3D substrate and tissue culture polystyrene (TCPS) as a 2D substrate. Although the expression level of the insulin, Glut2 and pdx‐1 genes in stem cells cultured on 3D substrate was significantly higher than the stem cells cultured on 2D substrate, the highest expression level of these genes was detected in the iPSCs cultured on PLGA‐PEG. Insulin and C‐peptide secretions from differentiated cells were also investigated and the results showed that secretions in cultured iPSCs on the PLGA‐PEG were significantly higher than cultured iPSCs on the TCPS and cultured MSCs on both PLGA‐PEG and TCPS. In addition, insulin protein was also expressed in the cultured iPSCs on the PLGA‐PEG significantly higher than cultured MSCs on the PLGA‐PEG. It can be concluded that differentiation potential of iPSCs into IPCs is significantly higher than human MSCs at both 2D and 3D culture systems. Abstract : In this study, the differentiation potential of the induced pluripotent stem cells (iPSCs) into IPCs was compared with mesenchymal stem cells (MSCs) while cultured on 2D and 3D substrates.3D substrate was poly(lactic‐co‐glycolic) acid/polyethylene glycol nanofibrous scaffold and 2D substrate was tissue culture polystyrene.Although the expression level of the genes, protein and insulin and C‐peptide secretions in stem cells cultured on 3D substrate was significantly higher than those stem cells cultured on 2D substrate, the highest expression level of these measures was detected in the iPSCs cultured on substrate compared to the MSCs.